Developing Extension Programming to Help Low-Income Families Save Money and Energy: The Community Weatherization Coalition Model - Paul Monaghan; Sarah Blucher; Marianne Schmink; Alane Humrich; Jennison Kipp; Wendell Porter (EDIS)
This new 3-page publication of the Department of Agricultural Education and Communication is the first in a series that will help Extension agents, nonprofits, agency personnel, and other promoters of community development better understand both the issue of high utility bills among low-income residents and what they can do to help. This first publication provides an overview of one program approach taken by a group of volunteers in Alachua County, the Community Weatherization Coalition, which uses a model of trained “energy coaches.” Written by Paul Monaghan, Sarah Blucher, Marianne Schmink, Alane Humrich, Jennison Kipp, and Wendell Porter. https://edis.ifas.ufl.edu/wc368